Diseño de una página web multimedia mediante fotografías y animaciones ilustradas, para difundir las costumbres y tradiciones del cantón Salcedo, provincia de Cotopaxi en el periodo 2014 - Taipe Cevallos, Cristian Roberto (2016)
This research project aims to disseminate and convey the customs and traditions of Salcedo Canton located in Cotopaxi Province to own people and strangers in this sector through the development of an website designed by different software in conjunction with graphic design skills acquired through university studies, this interactive application is easily accessible to users because it is located on the web and it is supported with factual information researched from its source. Users will strengthen their knowledge about the history of customs and traditions at Salcedo Canton with this interactive application including each of the parishes that comprise it, as well as its most representative festivities and typical food such as: the traditional "pinol" ice cream and "hornado" which are known at nationally and internationally level for its exquisite taste….